Virotherapy: current trends and future prospects for treatment of colon and rectal malignancies - Chin, Liang Lee; Veeramani, Sanggeetha; Molouki, Aidin; Swee, Hua Erin Lim; Thomas, Warren; Suet, Lin Chia; Yusoff, Khatijah (Taylor & Francis, 2019)
Colorectal cancer (CRC) is one of the most common malignancies. In recent decades, early diagnosis and conventional therapies have resulted in a significant reduction in mortality. However, late stage metastatic disease still has very limited effective treatment options. There is a growing interest in using viruses to help target therapies to tumour sites. In recent years the evolution of immunotherapy has emphasised the importance of directing the immune system to eliminate tumour cells; we aim to give a state-of-the-art over-view of the diverse viruses that have been investigated as potential oncolytic agents for the treatment of CRC.